Antioxidant status, oxidative stress, and damage in elite trained kayakers and canoeists and sedentary controls - Teixeira, V.; Valente, H.; Casal, S.; Marques, F.; Moreira, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
Strenuous physical activity is known to generate reactive oxygen species to a point that can exceed the antioxidant defense system and lead to oxidative stress. Dietary intake of antioxidants, plasma enzymatic (superoxide dismutase, glutathione reductase [Gr], and glutathione peroxidase [GPx]) activities, nonenzymatic (total antioxidant status [TAS], uric acid, a-tocopherol, retinol, ß-carotene, a-carotene, lycopene, and lutein + zeaxanthin) antioxidants, and markers of lipid peroxidation (thiobarbituricacid- reactive substances [TBARS]) and muscle damage (creatine kinase [CK]) were measured in 17 elite male kayakers and canoeists under resting conditions and in an equal number of age- and sex-matched sedentary individuals. Athletes showed increased plasma values of a-tocopherol (p = .037), a-carotene (p = .003), ß-carotene (p = .007), and superoxide dismutase activity (p = .002) and a lower TAS level (p = .030). Antioxidant intake (a-tocopherol, vitamin C, and ß-carotene) and plasmatic GPx, Gr, lycopene, lutein + zeaxanthin, retinol, and uric acid levels were similar in both groups. Nevertheless, TBARS (p < .001) and CK (p = .011) levels were found to be significantly higher in the kayakers and canoeists. This work suggests that despite the enhanced levels of antioxidants, athletes undergoing regular strenuous exercise exhibited more oxidative stress than sedentary controls.